Comprehensive geriatric assessment in the emergency department for the prediction of readmission among older patients: A 3-month follow-up study. (January 2021) - Huang, Hsien-Hao; Chang, Julia Chia-Yu; Tseng, Chien-Chien; Yang, Yu-Jie; Fan, Ju-Sing; Chen, Yen-Chia; Peng, Li-Ning; Yen, David Hung-Tsang
Highlights: Frailty was the only independent predictor for revisit/readmission after ED discharge during the 3-month follow up. For ED physicians, malnutrition and IADL were independent predictors in recognizing whether the older patient should be admitted to the hospital. For discharged elderly ED patients, frailty was the independent predictor for the integration of community services for older patients to decrease the rate of revisit/readmission in 3 months. Abstract: Background: Older people present to the emergency department (ED) with distinct patterns and emergency care needs. This study aimed to use comprehensive geriatric assessment (CGA) surveying the patterns of ED visits among older patients and determine frailty associated with the risk of revisits/readmission. Methods: This prospective study screened 2270 patients aged ≥75 years in the ED from August 2018 to February 2019. All patients underwent CGA. A 3-months follow-up was conducted to observe the hospital courses of admission and revisit/readmission. Results: A total of 270 older patients were enrolled. The independent predictors of admission at initial ED visit were the risk of nutritional deficit and instrumental activities of daily living (IADL). In the admission group, the independent predictors of revisit/readmission were a fall in the past year and mobility difficulties. In the discharge group, the independent predictors of revisit/readmission were frailty and insomnia. Regardless if older patients were either admitted or discharged at the initial ED visit, the independent predictor of revisit/readmission for older patients was frailty. Conclusion: Our study showed that frailty was the only independent predictor for revisit/readmission after ED discharge during the 3-month follow up. For ED physicians, malnutrition and IADL were independent predictors in recognizing whether the older patient should be admitted to the hospital. For discharged older ED patients, frailty was the independent predictor for the integration of community services for older patients to decrease the rate of revisit/readmission in 3 months.